Online food ordering system featuring chatbot for cafeteria UiTM Tapah / Azuwa Jalaludin, Azilawati Azizan and Nurkhairizan Khairudin - Jalaludin, Azuwa; Azizan, Azilawati; Khairudin, Nurkhairizan (Universiti Teknologi MARA Press (Penerbit UiTM), 2023)
The popularity of online food ordering systems has surged in recent years, offering a convenient solution for customers to place food orders from cafeterias. This trend is ideal for use in university cafeterias as well, which are typically overcrowded and noisy, particularly during peak hours. Therefore, this project aimed to address these challenges by designing a user-friendly web-based food ordering system in the context of cafeterias at the University Teknologi MARA (UiTM) Tapah Campus. The primary objective was to simplify the process for customers to select their desired meals, add them to a virtual cart, and effortlessly submit their orders and eliminating the need for long queues. The next objective is to enhance usability; hence, we integrated the Google Dialogflow chatbot feature into the website. The chatbot is an intelligent assistant that provides guidance, answers queries, and ensures a seamless ordering experience. The last objective is to validate the usability of the proposed system. Following the systems development life cycle (SDLC), our project successfully delivered an online food ordering system with an integrated chatbot for the universities’ cafeteria. The system addresses queuing issues, improves cafeteria operations, and enriches customer experiences. The system received about 70% positive feedback and was considered easy to access and use by most users. Meanwhile, the chatbot's usability produced highly positive feedback with 100% of the users thought the chatbot was easy to use and helpful.